Social and cultural changes in livelihood systems, resulting from the implementation of biocultural actions - Cuajera Nahui, Dario; Escóbar Vásquez, César Gabriel; Aguilar Colmenares, Ángel Richard (Agricultura, Sociedad y Desarrollo, 2022)
The situation of poverty of rural families and the growing demand for access to productive bases are causing socioecological transformations in livelihood systems. In recent years, public and private institutions have been implementing development actions which could have a positive or negative repercussion on the social and cultural life of rural families. The effects that development actions could cause on sociocultural aspects should be studied, to plan sustainable territorial management and thus reduce poverty and the pressure on natural resources. Sociocultural changes are seen in this case, resulting from the implementation of biocultural actions. The method used was mixed research: the qualitative variables were gathered in dialogue circles of knowledge, analyzed based on categories; the quantitative variables were collected with structured interviews, examined by comparison of two means, based on limits of confidence of an average. There are significant positive changes for qualitative indicators: organizational strength, valuation of local knowledge, and valuation of the satisfaction of food security. The quantitative indicators do not show changes: agricultural production, economic income or kilocalorie consumption. Understanding the qualitative or quantitative changes, positive or negative, will allow recovering knowledge for the integral management of livelihood systems.